Gender in Endocrine Diseases: Role of Sex Gonadal Hormones. (21st October 2018) - Lauretta, R.; Sansone, M.; Sansone, A.; Romanelli, F.; Appetecchia, M.
Abstract : Gender- and sex- related differences represent a new frontier towards patient-tailored medicine, taking into account that theoretically every medical specialty can be influenced by both of them. Sex hormones define the differences between males and females, and the different endocrine environment promoted by estrogens, progesterone, testosterone, and their precursors might influence both human physiology and pathophysiology. With the term Gender we refer, instead, to behaviors, roles, expectations, and activities carried out by the individual in society. In other words, "gender" refers to a sociocultural sphere of the individual, whereas "sex" only defines the biological sex. In the last decade, increasing attention has been paid to understand the influence that gender can have on both the human physiology and pathogenesis of diseases. Even the clinical response to therapy may be influenced by sex hormones and gender, but further research is needed to investigate and clarify how they can affect the human pathophysiology. The path to a tailored medicine in which every patient is able to receive early diagnosis, risk assessments, and optimal treatments cannot exclude the importance of gender. In this review, we have focused our attention on the involvement of sex hormones and gender on different endocrine diseases.